Free cooling based phase change material for domestic buildings in hot arid climate - Zeinelabdein, Rami; Omer, Siddig; Mohamed, Elamin; Amaireh, Ikrima; Gan, Guohui (2017)
Free cooling based phase change materials (FCPCM) are promising sustainable technologies which could be used to store the cold energy available during summer nights in a sufficient latent heat storage for later utilisation during the daytime. This current work aims to evaluate the feasibility of FCPCM technology in hot arid regions where the cooling demand is dominant during most of the year round. Energy-Plus simulation engine was used to predict the cooling load of a selected case study in order to size the capacity of the storage medium. The flat-plate PCM panel storage system has been developed and assessed using computational fluid dynamics (CFD) modeling utilising ANSYS FLUENT. The influence of operating conditions on the system performance was discussed through studying the solidification and melting process characterisation of the PCM. The results indicate that the proposed system is capable of reducing the cooling load substantially and the temperature of air supplied by the system is well maintained within the summer comfort zone between 298.65 and 303.15 K under the case study climate for up to 14.5 hours during the discharging period.